2020
DOI: 10.1371/journal.pbio.3000700
|View full text |Cite
|
Sign up to set email alerts
|

TRIC-A shapes oscillatory Ca2+ signals by interaction with STIM1/Orai1 complexes

Abstract: Trimeric intracellular cation (TRIC) channels have been proposed to modulate Ca 2+ release from the endoplasmic reticulum (ER) and determine oscillatory Ca 2+ signals. Here, we report that TRIC-A-mediated amplitude and frequency modulation of ryanodine receptor 2 (RyR2)-mediated Ca 2+ oscillations and inositol 1,4,5-triphosphate receptor (IP 3 R)-induced cytosolic signals is based on attenuating store-operated Ca 2+ entry (SOCE). Further, TRIC-A-dependent delay in ER Ca 2+ store refilling contributes to shapin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…Transcripts of the minor Tmem38b gene were found principally at the beginning of corticogenesis (E11–E13) and then declined ( Figure 3 C). TRIC-A has been shown to co-cluster with STIM1/Orai1 proteins and functions as negative modulator of store-operated Ca channels and oscillatory Ca 2+ signals [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Transcripts of the minor Tmem38b gene were found principally at the beginning of corticogenesis (E11–E13) and then declined ( Figure 3 C). TRIC-A has been shown to co-cluster with STIM1/Orai1 proteins and functions as negative modulator of store-operated Ca channels and oscillatory Ca 2+ signals [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…We observed an increase in oscillation frequency but a decrease in the average amplitude of these oscillations in neurons in the optic tectum in stim2a −/− zebrafish compared with WT fish. It was shown earlier that STIM2 deletion and the subsequent SOCE disruption caused the decrease in oscillations of non-neuronal cells [ 66 , 67 ]. However, our in vivo data showed the increased Ca 2+ oscillation frequency in brain neurons stim2a −/− mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Shrestha et al . reported that TRIC-A interacts with the STIM1/Orai1 complex and negatively regulates STIM1/Orai1 function [ 20 ]. They reported that TRIC-A modulates SOCE and oscillatory calcium signals by affecting the STIM1/Orai1 complex.…”
Section: Discussionmentioning
confidence: 99%